Using shells in the cult and economic activities of ancient population - Serikov Yu.B. (Вестник археологии, антропологии и этнографии, 2017)
The article is dedicated to one of the aspects of symbolic activities of ancient population regarding the use of a rare variety of natural material. From ancient times, shells, as bright and unusual material, served for making jewelry: bead necklaces and pendants. In the Urals, such artefacts had been used from the beginning of the Upper Paleolithic to the Modern Times. The shells rarely served as combs punches, scrapers and containers for paints. Petrified shells were very rare and unusual. That is why they were used in symbolic activities and could serve as amulets, cult symbols and communicative signs.